The circus infinite - Wong, Khan (Angry Robot, 2022)
A mixed-species fugitive, Jes tries to blend in on a pleasure moon, but instead catches the attention of a crime boss who owns the resort-casino where he lands a circus job and is forced to bend to the mobster's will until he decides to take the big boss down.